Aspectos críticos da aprendizagem de relações condicionais e emergência de equivalência de estímulos em crianças com deficiência visual - Canosa, Alessandra Corne (Universidade Federal de São Carlos, 2017)
The Study 1 investigated stimuli equivalence class expansion by two 5years-old visually impaired children. The stimuli were eigth auditory or tactil sets related to three animals: lion /elephant/ monkey. In five sets the stimuli had physical similarities between them and another two were composed by arbitrary stimuli. Conditional discriminations were taught using the matching-to- sample procedure (MTS), followed by equivalence, generalization, maintenance and class expansion tests. The data indicated the formation of three classes with eight stimuli. Study 2 replicated Study 1 with the objective of evaluatingthe formation of equivalence classes of auditory and tactile stimuli by a visually impaired child. Six sets of Study 1 were maintained, two excluded, and a new set with arbitrary stimuli was included. The results replicated the data of the previous study and evidenced the formation of equivalence classes with auditory and tactile stimuli. Study 3 aimed to document the formation of stimulus equivalence classes for infants children with visual impairments. Four sets of conventional stimuli, familiar and unfamiliar, were used, which did not present physical similarities among themselves. The simultaneous MTS procedure was used in attempts to test with tactile stimuli. A 46-month-old child was exposed to teaching and testing arbitrary relations between stimuli. Four sets of conventional stimuli, familiar and unfamiliar were used, which did not present physical similarities among themselves. The simultaneous MTS procedure was used in test’s trials with tactile stimuli. Sorting tests were administered as a secondary measure of class formation. The participant learned the conditional discrimination auditory-tactile and responded consistently to the assessment of the emergence of equivalence relations. Sorting tests confirmed the establishment of relationships between equivalent stimuli, in addition to attesting the maintenance of the classes after the period of twelve months. This work allowed the confirmation and expansion of the findings on equivalence classes in children with visual impairment and allowed that relevant variables in teaching procedures were identified. These data have important implications for the development of teaching technologies for this population.
Critical aspects of conditional relations learning and stimulus equivalence emergency in visually impaired children
Keywords: Equivalência de estímulos; Expansão de classes; Manutenção de classes; Criança; Deficiência visual; Stimulus equivalence; Class expansion; Class maintenance; Child; Visual impairment; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO DESENVOLVIMENTO HUMANO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL